2011
DOI: 10.5114/wiitm.2011.26255
|View full text |Cite
|
Sign up to set email alerts
|

Is the shear wave sonographic elastography correlated with pain after breast augmentation with silicone implants an indication of inflammatory activity? A preliminary report.

Abstract: IntroductionFormation of a capsule is a natural inflammatory response to a foreign body such as a breast implant. Breast capsular contracture is the most severe complication of implant surgery.AimTo evaluate breast tissues and the periprosthetic reaction with sonoelastography.Material and methodsNineteen patients aged 20-41 underwent breast augmentation with silicone-filled implants. Their 38 breasts were evaluated before surgery, and 7 and 14 days after surgery. Whole breast stiffness was measured by applanat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 18 publications
0
17
0
Order By: Relevance
“…32 The results of previous studies are in accordance with our findings. [33][34][35][36] Furthermore, the drainage time was mostly longer than 72 hours after surgery in our study, which was greater than the time reported in the literature (ie, 24-72 hours). 31,[34][35][36] Unfortunately, the use of postoperative drainage in breast augmentation is seldom specified in reports describing the electrosurgical method.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…32 The results of previous studies are in accordance with our findings. [33][34][35][36] Furthermore, the drainage time was mostly longer than 72 hours after surgery in our study, which was greater than the time reported in the literature (ie, 24-72 hours). 31,[34][35][36] Unfortunately, the use of postoperative drainage in breast augmentation is seldom specified in reports describing the electrosurgical method.…”
Section: Discussionmentioning
confidence: 83%
“…[33][34][35][36] Furthermore, the drainage time was mostly longer than 72 hours after surgery in our study, which was greater than the time reported in the literature (ie, 24-72 hours). 31,[34][35][36] Unfortunately, the use of postoperative drainage in breast augmentation is seldom specified in reports describing the electrosurgical method. [33][34][35][36] This may be because most augmentation mammaplasties are performed in the clinic, and no drainage tube is placed.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…The procedure was performed by a senior plastic surgeon between September 2010 and March 2011. The dual-plane surgical technique was used, as described previously [ 9 , 10 ].…”
Section: Methodsmentioning
confidence: 99%
“…The breast stiffness was also determined by applanation tonometry, and the value of the intramammary pressure was calculated from the formula P = F/A , where F is the force applied to the organ and A is the contact area of the disc, which weighed 213 g and had a diameter of 20.3 cm [ 9 , 10 ].…”
Section: Methodsmentioning
confidence: 99%